In silico and in vitro antiviral activity evaluation of prodigiosin from Serratia marcescens against enterovirus 71 - Muhamad Fakrulnizam Abd Aziz,; Chee, Wai Yip; Norefrina Shafinaz Md Nor, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Prodigiosin, a red linear tripyrrole pigment found in Serratia marcescens, is one such naturally occurring compound that has gained wide attention owing to its numerous biological activities, including antibacterial, antifungal, antimalarial, anticancer, and immunosuppressive properties. This study was conducted to evaluate the possible antiviral activity of prodigiosin against Enterovirus 71, a causative agent of hand, foot, and mouth disease (HFMD). Preliminary studies were done in silico by analyzing the interaction of prodigiosin with amino acid residues of five EV71-target proteins. Interaction refinement analysis with FireDock revealed that 2C helicase (-48.01 kcal/moL) has the most negative global energy, followed by capsid (-36.52 kcal/moL), 3C protease (-34.16 kcal/moL), 3D RNA polymerase (-30.93 kcal/moL) and 2A protease (-20.61 kcal/moL). These values are indicative of the interaction strength. Prodigiosin was shown to form chemical bonds with specific amino acid residues in capsid (Gln-30, Asn-223), 2A protease (Trp-33, Trp-142), 2C helicase (Tyr-150, His-151, Gln-169, Ser-212), 3C protease (Glu-50), and 3D RNA polymerase (Ala-239, Tyr-237). To investigate further, prodigiosin was extracted from S. marcescens using a methanolic extraction method. In vitro studies revealed that prodigiosin, with an IC50 value of 0.5112 μg/mL, reduced virus titers by 0.17 log (32.39%) in 30 min and 0.19 log (35.43%) in 60 min. The findings suggest that prodigiosin has antiviral activity with an intermediate inhibitory effect against EV71. As a result of this research, new biological activities of prodigiosin have been identified.